Combining Artificial Intelligence and Remote Sensing to Enhance the Estimation of Peanut Pod Maturity - Oliveira, Thiago Caio Moura [UNESP]; Souza, Jarlyson Brunno Costa [UNESP]; de Almeida, Samira Luns Hatum [UNESP]; de Brito Filho, Armando Lopes [UNESP]; de Souza Silva, Rafael Henrique [UNESP]; Carneiro, Franciele Morlin; da Silva, Rouverson Pereira [UNESP] (MDPI, 2025)
The mechanized harvesting of peanut crops results in both visible and invisible losses. Therefore, monitoring and accurately determining pod maturation are essential to minimizing such losses. The objectives of this study were to (i) identify the most relevant variables for estimating peanut pod maturation and (ii) estimate two maturation indices (brown and black classes; orange, brown, and black classes) using Remote Sensing (RS) and Artificial Neural Networks (ANN), while assessing the generalization potential of the models across different areas. The experiment was carried out in two commercial peanut fields in the state of São Paulo, Brazil, during the 2021/2022 and 2022/2023 growing seasons, using the IAC 503 cultivar. Data collection began one month before the expected harvest date, with weekly intervals. Spectral variables and vegetation indices were obtained from orbital remote sensing (PlanetScope), while climatic data were retrieved from NASA POWER. For analysis, two ANN architectures were employed: Multilayer Perceptron (MLP) and Radial Basis Function (RBF). The dataset from the Cândido Rodrigues site was split into 80% for training and 20% for testing. The model was then evaluated and generalized using data from the Guariba site. Variable selection involved filtering via Principal Component Analysis (PCA) followed by the Stepwise method. Both models demonstrated high accuracy (R2 ≥ 0.90; MAE between 0.06 and 0.07). Generalization tests yielded promising results (R2 between 0.59 and 0.64; MAE between 0.13 and 0.17), confirming the robustness of the approach under different conditions.